Modulation of the intrinsic chromatin binding property of HIV-1 integrase by LEDGF/p75. Issue 19 (11th October 2021) - Lapaillerie, Delphine; Lelandais, Benoît; Mauro, Eric; Lagadec, Floriane; Tumiotto, Camille; Miskey, Csaba; Ferran, Guillaume; Kuschner, Natacha; Calmels, Christina; Métifiot, Mathieu; Rooryck, Caroline; Ivics, Zoltan; et al.
Abstract: The stable insertion of the retroviral genome into the host chromosomes requires the association between integration complexes and cellular chromatin via the interaction between retroviral integrase and the nucleosomal target DNA. This final association may involve the chromatin-binding properties of both the retroviral integrase and its cellular cofactor LEDGF/p75. To investigate this and better understand the LEDGF/p75-mediated chromatin tethering of HIV-1 integrase, we used a combination of biochemical and chromosome-binding assays. Our study revealed that retroviral integrase has an intrinsic ability to bind and recognize specific chromatin regions in metaphase even in the absence of its cofactor. Furthermore, this integrase chromatin-binding property was modulated by the interaction with its cofactor LEDGF/p75, which redirected the enzyme to alternative chromosome regions. We also better determined the chromatin features recognized by each partner alone or within the functional intasome, as well as the chronology of efficient LEDGF/p75-mediated targeting of HIV-1 integrase to chromatin. Our data support a new chromatin-binding function of integrase acting in concert with LEDGF/p75 for the optimal association with the nucleosomal substrate. This work also provides additional information about the behavior of retroviral integration complexes in metaphase chromatin and the mechanism of action of LEDGF/p75 in this specific context.